EMI-shielding response of GO/Fe3O4/polypyrrole(PPy)/thermoplastic polyurethane (TPU) composites - Kaftelen-Odabasi, H.; Ruiz-Perez, F.; Odabasi, A.; Helhel, S.; Lopez-Estrada, S. M.; Caballero-Briones, F. (Elsevier - Division Reed Elsevier India Pvt Ltd, 2024)
In the present study, thermoplastic polyurethane was reinforced with GO/Fe3O4/PPy nanocomposites with varying GO:Fe3O4 ratio to develop high-performance electromagnetic interference (EMI) shields. GO/Fe3O4/PPy fillers were prepared by adding polypyrrole (PPy) nanotubes, synthesized by the soft-template method from oxidative polymerization of pyrrole, to graphene oxide decorated with Fe3O4 nanoparticles prepared by a sonochemical method. X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Raman spectroscopy were performed to reveal the structural and morphological properties of GO/Fe3O4/PPy nanofillers, and the structure and thermal properties of the GO/Fe3O4/PPy/TPU nanocomposites was studied by cryofracture SEM and thermogravimetry (TGA). The effect of GO:Fe3O4 ratio on the electrical conductivity, magnetic permeability, permittivity, and electromagnetic-wave-shielding performance of GO/Fe3O4/PPy/TPU nanocomposites was investigated in the Xband frequency range. The maximum EMI efficiency was 4.81 dB with increasing GO:Fe3O4 ratio in GO/Fe3O4/ PPy/TPU composites, with blocking of 66.72 % of the incident electromagnetic wave.
Keywords: Electromagnetic shielding; Thermoplastic composites; Shielding efficiency; GO/Fe (3) O (4) /PPy nanofillers